Studi Kelayakan Video Klip Bayi di Manado Sulawesi Utara - Soewignyo, Fanny (JBE (Journal of Business and Economics); Volume 7 No.1, 2008 JBE UNKLAB, 2008)
This study aims to look into the possibility of doing baby born video clip business in Manado, Sulawesi utara as a franchisee by purchasing the patent right from Creator Production, Jakarta, the holder of the right from Government. The target market of this business is the families who are expecting of baby born with middle level income and above. The unique of this business is its concern about ethics and professionalism related to client’s privacy. All employees, especially those who will handle the camera, the crew, and editors must be women. The potential competitors are those conducting video photography business in general. Based on projected financial reports: the balance sheet, the income statement, and the statement of cash flows is prepared with the related ratio analysis. These reports would be helpful to the potential investors before putting their money into the start-up business and according to the projected financial reports and ratio analysis this business is protifatable.